Reduced basal and increased topdressing fertilizer rate combined with straw incorporation improves rice yield stability and soil organic carbon sequestration in a rice–wheat system - Zhang, Jianwei; Wang, Jidong; Zhou, Yan; Xu, Lei; Chen, Yinglong; Ding, Yanfeng; Ning, Yunwang; Liang, Dong; Zhang, Yongchun; Li, Ganghua (Frontiers in Plant Science, 2022)
Fertilizer management is vital for sustainable agriculture under climate change. Reduced basal and increased topdressing fertilizer rate (RBIT) has been reported to improve the yield of in-season rice or wheat. However, the effect of RBIT on rice and wheat yield stability and soil organic carbon (SOC) sequestration potential is unknown, especially when combined with straw incorporation. Here, we report the effect of RBIT with/without straw incorporation on crop yields, yield stability, SOC stock, and SOC fractions in the lower Yangtze River rice-wheat system region over nine years. RBIT with/without straw incorporation significantly increased nine-year average and annual rice yields but not wheat yields. Compared with conventional fertilization (CF), RBIT did not significantly affect wheat or rice yield stability, but combined with straw incorporation, it increased the sustainable yield index (SYI) of wheat and rice by 7.6% and 12.8%, respectively. RBIT produced a higher C sequestration rate (0.20 Mg C ha−1 year−1) than CF (0.06 Mg ha−1 year−1) in the 0–20 cm layer due to higher root C input and lower C mineralization rate, and RBIT in combination with straw incorporation produced the highest C sequestration rate (0.47 Mg ha−1 year−1). Long-term RBIT had a greater positive effect on silt+clay (0.053 mm)-associated C, microbial biomass C (MBC), dissolved organic C, and hot water organic C in the surface layer (0–10 cm) than in the subsurface layer (10–20 cm). In particular, the increases in SOC pools and mean weight diameter (MWD) of soil aggregates were greater when RBIT was combined with straw incorporation. Correlation analysis indicated that topsoil SOC fractions and MWD were positively correlated with the SYI of wheat and rice. Our findings suggest that the long-term application of RBIT combined with straw incorporation contributed to improving the sustainability of rice production and SOC sequestration in a rice-wheat system.